Spatial and temporal variations of refractory black carbon along the transect from Zhongshan Station to Dome A, eastern Antarctica. (1st December 2020) - Ma, Xiangyu; Li, Chuanjin; Du, Zhiheng; Dou, Tingfeng; Ding, Minghu; Ming, Jing; Wang, Mo; Gao, Shaopeng; Xiao, Cunde; Wang, Xiaoming; Ren, Jiawen; Kang, Shichang
Abstract: Refractory black carbon (rBC) aerosols emitted by biomass burning and fossil fuel combustion can cause significant climatic forcing when it deposited on the snow. The Southern Hemisphere (SH) biomass burning emissions represent a significant part of rBC in and around Antarctica. Here we present the spatial and temporal variations of rBC from the surface snow and snow pits samples along the coastal Zhongshan Station (ZSS) to inland Dome A transect in Lambert Glacier region of eastern Antarctica. The geometric mean concentrations of surface snow rBC was 0.017 ± 0.018 ng g −1 and showed higher values in the inland plateau region (900–1248 km, 0.031 ± 0.024 ng g −1 ) than the coastal region (0–400 km, 0.011 ± 0.005 ng g −1 ) and there exist similar spatial results for the inland snowpit (0.021 ± 0.017 ng g −1 ) and coastal snowpit (0.018 ± 0.013 ng g −1 ). The records from the coastal snowpit (SP-A) show that the rBC from 2009 to 2016 displays weak seasonal variations, while in the inland snowpit (SP–C) the records spans from 1950 to 2015 and showed the rBC concentrations vary and relate with the open biomass burning emission in the Southern Hemisphere. Highlights: Spatial and temporal variations of the rBC along the transect from ZSS to Dome A in eastern Antarctica were retrieved. Higher geometric mean rBC concentrations in the interior section than the coastal section were detected. Dome A rBC record during 1950 and 2015 shows good relation with the open biomass burning in the Southern Hemisphere.